Inhibition of Orai-STIM coupling alleviates experimentally-induced airways remodeling changes - Martina Sutovska; Sona Franova (Revista Alergia México, 2018)
Background: In asthma, airway remodeling changes contribute to thickening of airway walls and, consequently, lead to poor clinical outcomes among asthmatic patients. Airway remodeling changes include subepithelial fibrosis, increased smooth muscle mass, gland enlargement, neovascularization and epithelial alterations. All these processes are mediated though the Ca2+-dependent pathways. Recently Orai-STIM coupling was proposed as one of the extracellular Ca2+ main sources that mediated airway remodeling.